A mídia como ator no processo de criminalização do partido dos trabalhadores nas Eleições de 2014 - Bibini, Adriana Barilari (2017)
The intention of this paper is that based on an analysis of the media coverage of the 2014 presidential elections, by means of communication vehicles such as the newspapers Folha de S. Paulo, O Estado de São Paulo Which is a website of the Laboratory of Media and Public Sphere Studies (LEMEP), in which the same is dedicated to accompanying the media coverage of the 2014 elections produce a journal of political coverage in the mainstream media and with this analysis, linked to the term Of the Policy Representation Scenario - CRP, to identify the media approach and whether it had a relevant weight in the image of negative and criminalization of the PT in the electoral period